1976
DOI: 10.1002/1097-0142(197609)38:3<1402::aid-cncr2820380346>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent cystosarcoma phyllodes.A clinicopathologic study of 32 cases

Abstract: A retrospective study was made of recurrent mammary cystosarcoma phyllodes seen at Memorial Sloan-Kettering Cancer Center from 1932 to 1972. C h icopathologic findings, clinical course, treatment, and survival are described. It is apparent that cystosarcomas may recur and several years may elapse between recurrences. We found that 18% of the benign and 8% of the malignant cystosarcomas recurred and malignant "transformation" occurred in two of the 28 recurrent benign cystosarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
2
12

Year Published

1978
1978
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 5 publications
6
61
2
12
Order By: Relevance
“…However, some can also exhibit a malignant clinical behavior with local recurrences and distant metastatic spread. 2 The histologic characteristics of the stroma determine whether a tumor is classified as benign or malignant. 3,4 The spectrum of stromal morphologies is very broad, from obviously benign with only moderately cellular stroma lacking atypia and mitoses; to frankly malignant with highly cellular stroma rich in mitoses and heterologous differentiation, as seen in other soft tissue sarcomas.…”
mentioning
confidence: 99%
“…However, some can also exhibit a malignant clinical behavior with local recurrences and distant metastatic spread. 2 The histologic characteristics of the stroma determine whether a tumor is classified as benign or malignant. 3,4 The spectrum of stromal morphologies is very broad, from obviously benign with only moderately cellular stroma lacking atypia and mitoses; to frankly malignant with highly cellular stroma rich in mitoses and heterologous differentiation, as seen in other soft tissue sarcomas.…”
mentioning
confidence: 99%
“…[25,47] Whether LR is a predictor for the development of systemic metastasis remains a controversial issue. Some authors have shown that up to 60% of patients with systemic metastasis develop prior LR, [25,[48][49][50] while some others refute this association. [10,11,23] LR or factors affecting LR may adversely affect survival for PT as well, similar to breast cancer.…”
Section: Histological Classificationmentioning
confidence: 67%
“…Table 34-4 summarizes collected series of CSPs in the literature with observed rates of local recurrence following excision. [92][93][94][95][96][97][98] The local recurrence rate is quite variable, partly owing to differences in extent of surgical resection undertaken. The cornerstone of the surgical approach to CSP is wide local excision with histologically negative margins.…”
Section: What Are the Treatment And Prognosis Of Cystosarcoma Phyllodes?mentioning
confidence: 99%